Agency Narrative of the Dangdut Koplo Singer on Stage - Endah Siswati; Rachmah Ida; Mustain (MOZAIK HUMANIORA, 2022)
This study started from the skepticism of the thought which states that work as female entertainers (dangdut koplo singers) puts women as objects and victims. Based on the thoughts of Sarah Drew Lucas about narrative agency which believes that every woman has the capacityÂ  Â as an autonomous agent, the researcher wants to explore another possibility that dangdut koplo singers are active subjects or autonomous agents by revealing the narrative of their lives on stage. The focus of this research is on how the female dangdut koplo singer does her job, how she builds and plays her existence on the performance stage, how oppression (subordination, marginalization, objectification, stigmatization) is faced, and how she negotiates to overcome oppression that threatens her capacity as autonomous agent. Researchers conducted in-depth interviews with a research subject and participant observations on the stage of dangdut koplo in East Java from late 2017 to late 2019. This research found that the research subject is a narrative agent who has the capacity to understand herself as "I" among other "I". The research subject is able to read and understand the plurality of life on the stage, and with that awareness and understanding perform actions in her own way which shows her identity. In conclusion, these findings confirm Sarah Drew Lucas's thought that being an agent is a necessity for women, no matter how oppressed or how tied they are to subordinate power relations.